2011
DOI: 10.1002/cncr.26440
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of continuous once‐daily dosing of sunitinib as first‐line treatment in patients with metastatic renal cell carcinoma

Abstract: BACKGROUND: Sunitinib at 50 mg/day on the 4-weeks-on-2-weeks-off schedule is the current approved regimen for advanced/metastatic renal cell carcinoma (mRCC). Escudier et al reported that continuous, once-daily dosing with sunitinib 37.5 mg had a manageable safety profile and significant antitumor activity as second-line mRCC therapy. In this prospective, multicenter, phase II study, we evaluated the activity of continuous once-daily dosing with sunitinib 37.5 mg as first-line mRCC treatment. METHODS: One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 24 publications
(51 reference statements)
1
58
2
Order By: Relevance
“…The most commonly reported treatment-related AEs were diarrhea (50%) and HFS (43%). The most commonly reported grade 3-4 treatment-related AEs were HFS (13%), neutropenia (11%) and diarrhea (9%) [14]. A recent randomized phase II study comparing a 37.5-mg CDD regimen to the 4/2 schedule (EFFECT trial) demonstrated no differences in drug tolerance or patient-reported symptoms, but showed a trend toward superiority of the 4/2 schedule over CDD in time to tumor progression (9.9 months for 4/2 schedule versus 7.1 months for CDD, HR 0.77, 95% CI 0.57-1.04, P = 0.09).…”
Section: Annals Of Oncology Reviewsmentioning
confidence: 99%
“…The most commonly reported treatment-related AEs were diarrhea (50%) and HFS (43%). The most commonly reported grade 3-4 treatment-related AEs were HFS (13%), neutropenia (11%) and diarrhea (9%) [14]. A recent randomized phase II study comparing a 37.5-mg CDD regimen to the 4/2 schedule (EFFECT trial) demonstrated no differences in drug tolerance or patient-reported symptoms, but showed a trend toward superiority of the 4/2 schedule over CDD in time to tumor progression (9.9 months for 4/2 schedule versus 7.1 months for CDD, HR 0.77, 95% CI 0.57-1.04, P = 0.09).…”
Section: Annals Of Oncology Reviewsmentioning
confidence: 99%
“…In the subgroup of patients who received one TKI, median PFS in everolimus group was 5.4 months, and in group who received two TKI-s 4 months. This was statistically significant longer than in placebo groups, where PFS was 1.9 and 1.8 months respectively [8,20,[36][37][38].…”
Section: Mtor Inhibitor After First Line Vegf-tkimentioning
confidence: 75%
“…Di Lorenzo and colleagues indirectly compared survival benefit in patients on everolimus or sorafenib in the second line. Median overall survival was 81.5 weeks for patients receiving everolimus and 32.0 weeks for sorafenib [37].…”
Section: Mtor Inhibitor After First Line Vegf-tkimentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous dosing of sunitinib (37.5 mg orally daily) demonstrated antitumor activity with a manageable safety profile in first and second-line mRCC appearing to be an alternative dosing strategy (Escudier, Roigas, et al, 2009), (Barrios et al, 2011). Phase II EFFECT trial compared the two dosing strategies; sunitinib 50 mg taken daily on 4/2 schedule versus 37.5 mg taken daily continuously in treatment naive mRCC (R. Motzer et al, 2011 A randomized phase II discontinuation trial in 225 patients who were either treatment naïve or progressed on prior cytokine or bevacizumab containing regimen showed durability and tolerability of the agent at a dose of 800 mg once daily with an overall response rate of 35% and median duration of response of 52 weeks .…”
Section: Sunitinibmentioning
confidence: 99%